2015
DOI: 10.1007/s13213-015-1111-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bacterial community structure in seawater pond with shrimp, crab, and shellfish cultures and in non-cultured pond in Ganyu, Eastern China

Abstract: The aim of this study was to gain an understanding of the effects of mariculture on the bacterial communities in a co-culture pond, which is a popular culture model for shrimp, crab, and shellfish along the eastern coast of China. Six seawater samples were collected from a pond with cultures of shrimp, crab, and shellfish, and six other samples were collected from a non-cultured pond (control). The diversity of the bacterial communities in the samples was examined using the MiSeq desktop sequencer (Illumina) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 61 publications
2
15
2
Order By: Relevance
“…A lot of studies have been done to analyse the composition of bacterial communities in aquaculture environment. For example, in a polyculture pond of shrimp, crab and shellfish, the dominant communities in the water were Proteobacteria, Chloroflexi, Actinobacteria, Firmicutes and Acidobacteria (Li, Yan, et al, ). Proteobacteria, Gemmatimonadetes and Actinobacteria were the top three phyla in the sediment of shrimp ponds in Mexico (Cornejogranados et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A lot of studies have been done to analyse the composition of bacterial communities in aquaculture environment. For example, in a polyculture pond of shrimp, crab and shellfish, the dominant communities in the water were Proteobacteria, Chloroflexi, Actinobacteria, Firmicutes and Acidobacteria (Li, Yan, et al, ). Proteobacteria, Gemmatimonadetes and Actinobacteria were the top three phyla in the sediment of shrimp ponds in Mexico (Cornejogranados et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, more diverse phyla were detected in sediment samples by the order of Bacteroidetes, Actinobacteria, Chloroflexi, Firmicutes, Acidobacteria, Cyanobacteria and Fusobacteria, which occupied 19.2%, 7.7%, 4.7%, 3.7%, 2.1%, 1.9% and 1.1% of total bacterial Chloroflexi, Actinobacteria, Firmicutes and Acidobacteria (Li, Yan, et al, 2016b). Proteobacteria, Gemmatimonadetes and Actinobacteria were the top three phyla in the sediment of shrimp ponds in Mexico (Cornejogranados et al, 2017).…”
Section: The Dominant Composition Of Bacterial Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the detrimental impacts of intensive aquaculture farming on environments, the development of ecofriendly polyculture systems is necessary for the sustainability of aquaculture practices although it may also alter the environments and, as a result, affect microbes. A previous study by Li, Yan, Li, Xu, and An () suggested the great influence of polyculture of shrimp, crab and shellfish on the seawater bacterial communities in pond by comparing with a non‐cultured treatment. In this study, the varying effects of polyculture systems with different biomass of fish–crab on the sediments were tested by comparing with each other and with a non‐cultured control treatment in the Dongping lake.…”
Section: Discussionmentioning
confidence: 99%